Along the No. 20 Line: Reminiscences of the Vancouver Waterfront - Knight, Rolf (New Star Books, 2011)
In Along the No. 20 Line, Rolf Knight takes the reader on a tour through working-class East Vancouver of a century ago. Knight's "through-line" is literally a line: the old No. 20 streetcar route that ran between downtown Vancouver and the present-day neighbourhood of the Pacific National Exhibition. From 1892 to 1949, when it was shut down and replaced by the No. 20 Granville / Victoria Drive bus, the No. 20 streetcar carried thousands of Vancouverites back and forth between their East Van homes and their jobs on the docks, and in the mills, factories, and workshops along the No. 20 line. –Publisher's description
OCLC: 751635542